2021
DOI: 10.2138/am-2021-7690
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure, halogen-bearing melt preserved in ultrahigh-temperature felsic granulites of the Central Maine Terrane, Connecticut (U.S.A.)

Abstract: Inclusions of relic high pressure melts provide crucial information on the fate of crustal rocks in the deep roots of orogens during collision and crustal thickening, including at extreme temperature conditions exceeding 1000°C. However, discoveries of high pressure melt inclusions are still a relative rarity among case studies of inclusions in metamorphic minerals. Here we present the results of experimental and microchemical investigations of nanogranitoids in garnets from the felsic granulites of the Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 57 publications
7
23
0
Order By: Relevance
“…Nanogranitoids were successfully rehomogenized in the multianvil apparatus at 1000°C and 4.5 GPa, the minimum conditions expected for the formation of the garnet in the Erzgebirge UHP unit ( 24 ), and thus likely to correspond to the entrapment conditions of the melt. The attained rehomogenization confirms that garnet and melt were both stable at the metamorphic peak conditions as demonstrated in previous studies ( 19 , 27 , 29 ). Preserved and rehomogenized glassy inclusions are granitic in composition, rich in alkalis [Na 2 O + K 2 O = 9.31 weight % (wt %) and Na 2 O/K 2 O = 0.75], and slightly peraluminous [alumina saturation index: molar Al 2 O 3 /(Na 2 O + K 2 O + CaO) = 1.10] and have a low magnesium number (Mg# = 27; see table S2).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Nanogranitoids were successfully rehomogenized in the multianvil apparatus at 1000°C and 4.5 GPa, the minimum conditions expected for the formation of the garnet in the Erzgebirge UHP unit ( 24 ), and thus likely to correspond to the entrapment conditions of the melt. The attained rehomogenization confirms that garnet and melt were both stable at the metamorphic peak conditions as demonstrated in previous studies ( 19 , 27 , 29 ). Preserved and rehomogenized glassy inclusions are granitic in composition, rich in alkalis [Na 2 O + K 2 O = 9.31 weight % (wt %) and Na 2 O/K 2 O = 0.75], and slightly peraluminous [alumina saturation index: molar Al 2 O 3 /(Na 2 O + K 2 O + CaO) = 1.10] and have a low magnesium number (Mg# = 27; see table S2).…”
Section: Resultssupporting
confidence: 89%
“…( A ) H 2 O (wt %) and CO 2 (ppm) content of glass and a rehomogenized (indicated with an asterisk) nanogranitoid from Saidenbach eclogites measured and corrected by NanoSIMS (error bar smaller than the symbol) and compared with H 2 O and CO 2 contents of lower continental crust melt inclusions in granulites [Central Maine Terrane (CMT) ( 19 ), Ivrea Zone ( 20 ), and Gruf Complex ( 61 )]. See table S5 for volatiles data, and for NanoSIMS calibration curves, see fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quartz-absent rocks containing mineral assemblages of garnet + spinel + corundum are not commonly discussed in the literature, although such rocks have been reported in several field areas (Asami et al, 1989(Asami et al, , 1990Dharmapriya et al, 2015;Dorfler et al, 2014Dorfler et al, , 2015Harris, 1981;Keller & Ague, 2018;Osanai et al, 2006;Ouzegane et al, 2003;Schreyer et al, 1984;Sengupta et al, 1999;Shimpo et al, 2006;Snoeyenbos et al, 1995). In a study based on phase equilibrium modelling and ternary feldspar thermometry in conjunction with textural observations, Keller and Ague (2018) obtained neareclogite-facies peak metamorphic conditions ($1040 C and $18 kbar) from quartz-absent garnet-spinel-corundum gneiss in the Central Maine Terrane, Connecticut, USA, and a recent study further confirmed these HP-UHT conditions using evidence from melt inclusions (Ferrero et al, 2021). Thus, for corundum-bearing rocks, multiple independent methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing recognition that lithologies with seemingly disparate records of metamorphic conditions in metamorphic terranes may have experienced the same history and differentially re-equilibrated (e.g. Arab et al, 2021;Ferrero et al, 2021). The occurrence of eclogite and HP granulite in migmatite terranes may be evidence that the exhumed material was deeply sourced despite the apparent LP-HT equilibration conditions of the migmatites.…”
Section: Introductionmentioning
confidence: 99%